Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Programa de Acção Social Produtiva (PASP) - Documento Base - INAS - Instituto Nacional de Acção Social (Ministério da Mulher e da Acção Social, República de Moçambique, 2012)
O presente documento surge assim como um instrumento de operacionalização do PASP visando clarificar as intervenções deste programa que é mais uma contribuição da segurança social básica para os esforços do Governo no combate à pobreza, alinhando-se com outras intervenções em curso, como por exemplo, o Programa Estratégico de Redução da Pobreza Urbana (PERPU), o Fundo de Desenvolvimento Distrital (FDD) e o Programa Nacional de insumos Agrícolas. O PASP procura contribuir para a superação da insegurança alimentar crónica agravada pelos choques e riscos estruturais e impactos das mudanças ambientais, como as secas, desemprego, permitindo que os agregados familiares abrangidos tenham estabilidade económica e social. O PASP toma como alvo de intervenção os Agregados Familiares (AF) com pelo menos um elemento com capacidade para o trabalho, enfrentando altos níveis de vulnerabilidade, com prioridade para os agregados chefiados por mulheres, por pessoas com deficiências e com crianças com problemas de desnutrição, que estejam localizados nas zonas urbanas e rurais, a partir do envolvimento destes em trabalhos públicos como principal veículo para a disponibilização de transferências sociais monetárias que lhes permitam estabilizar o seu rendimento e consumo. Os mesmos agregados familiares são encorajados em seguida a se envolverem em iniciativas de geração de rendimentos através de um conjunto de acções enquadradas num processo de preparação social para a graduação. O presente documento desenvolve o modelo de intervenções do PASP, os seus objectivos, componentes, nomeadamente, trabalhos públicos com o uso da mão-de-obra intensiva e apoio ao desenvolvimento de iniciativas de geração de rendimentos, as ligações necessárias entre este. Programa e outros processos no âmbito do combate à pobreza, bem como os mecanismos de implementação, financiamento e os factores críticos de sucesso do Programa.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

Promoting SME development in Indonesia - Mourougane, Annabelle (OECD Economics Department Working Papers, 2012)
Micro, small and medium-sized firms (MSMEs) are a key source of employment and economic growth in Indonesia. They contributed to the country’s economic resilience during the 2008-09 financial crisis. But many suffer from low productivity, curbing their role in boosting living standards. There are several ways to spur MSME productivity growth over the medium term. The first route would be to encourage the formalisation of small firms. Lessening red tape through simplification of the licensing process and lower tax compliance costs would help. Avoiding excessive rises in the minimum wage in provinces where it is already at a reasonable level would also be important. Looking forward, it would be useful to remove rigidities in the formal labour markets, while moving to some form of unemployment benefit system to insure workers against job-loss risks. The second route would be to boost investment. Clarifying property rights for real estate, and making the information collected by the credit bureau available to all financial institutions would ease access to finance. At the same time, the development of financing alternatives such as venture capital, leasing or micro-finance would enhance credit supply. The poor state of infrastructure, in particular in the transportation and electricity sectors, is also perceived as an important impediment to investment and could be remedied by increasing public infrastructure spending on cost-effective projects. The third route would be to enhance the quality of human resources. The country suffers from a lack of skilled workers, and policies should aim both at increasing the pool of workers and making education and training institutions more responsive to evolving labour-market demand. Indonesia has a long tradition of supporting MSMEs. But responsibilities between the different levels of government and within the central government need to be clarified to minimise overlap and inefficiencies. A rigorous assessment of existing programmes would allow schemes to be consolidated and scarce public funds to be directed to their most cost-effective uses.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Avaliação Conjunta do: Apoio à Participação da Sociedade Civil no Diálogo sobre Políticas - ITAD; COWI (ITAD/COWI, 2012)
Estudo de Caso 1. Planificação Distrital e Monitoria do Orçamento Planificação Distrital e Monitoria do Orçamento são processos interligados mas distintos. A Planificação Distrital é um processo de política ao abrigo da LOLE1, segundo a qual a participação das comunidades locais é um princípio básico na governação local e gestão de bens públicos. A planificação distrital é um processo simples, no qual a sociedade civil (SC) local é representada através dos Conselhos Consultivos Locais. O processo de planificação é muitas vezes uma “lista de compras”, sem ligação com a definição de prioridades do orçamento, que é feita ao nível do governo central ou provincial, muitas vezes depois de a planificação ter sido feita a nível distrital. A monitoria sistemática do orçamento é um exercício recente em Moçambique, embora tenha já sido feita sob os auspícios de várias projectos apoiados por Organizações Internacionais da Sociedade Civil (OISCs). Baseia-se na experiência da SC em vários mecanismos de diálogo sobre políticas (por exemplo, Observatórios de Desenvolvimento (ODs)). Estudo de Caso 2. Legislação sobre Violência Doméstica A violência contra a mulher (VCM), em geral, e a violência doméstica contra as mulheres, em particular, constituem um problema global. Em Moçambique, é uma prática generalizada e, infelizmente, largamente aceite, que assenta em sólidos papéis tradicionais de género. Isto é testemunhado por estudos e casos documentados recolhidos por OSCs (WLSA, Le Musica), e por estatísticas dos Gabinetes de Atendimento para mulheres vítimas de violência37. Os casos de violência doméstica contra as mulheres eram, porém, vistos como pertencendo à esfera doméstica (privada) e, assim sendo, não eram considerados uma questão pública; e, até recentemente, não havia nenhum enquadramento jurídico da questão.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género

The Human Rights Impacts of Tree Plantations in Niassa Province, Mozambique - Seufert, Philip; Santos, Ricardo (FIAN International, 2012)
This study investigates the impairing of the rights of peasant communities through the establishment of tree plantations in Niassa province, Mozambique. More particularly, it looks at the impacts of the operations of Chikweti Forests of Niassa on the local population in the districts of Lago, Lichinga and Sanga. In order to do so, it presents an introductory chapter on the general context of Mozambique and the legal framework. This legal framework will serve as a basis on the analysis of the findings of this study using a human rights approach. It contains an overview of national and international provisions relevant to the case. This includes Mozambican national legislation and policies, as well as standards under international human rights law. Regarding the latter, it puts a particular focus on extraterritorial obligations (ETOs), recently clarified by the Maastricht Principles on Extraterritorial Obligations, and includes provisions related to access to land and related resources, as contained in the Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; rural development / desenvolvimento rural

Saúde Para O Povo? Para Um Entendimento Da Economia Política E Das Dinâmicas Da Descentralização No Sector Da Saúde Em Moçambique - Weimer, Bernhard (Moçambique: Descentralizar o Centralismo? Economia Política, Recursos E Resultados, 2012)
Houve em 2011 três acontecimentos que revelaram as dimensões dos desafios que se colocam à gestão do Sistema Nacional de Saúde moçambicano em geral e ao Ministério de Saúde (MISAU) em particular. O primeiro foi uma auditoria externa das contas de 2009 do PROSAUDE II e do Fundo Global, realizada pela empresa de auditoria KPMG e entregue ao governo e aos seus parceiros internacionais em Junho de 2011. Esta auditoria revelou fraquezas consideráveis, nomeadamente em relação à auditoria interna e uma substancial diferença final não reconciliada entre os valores recebidos e os pagamentos efectuados. O segundo foi a crise de abastecimento de medicamentos, amplamente divulgada dos produtos farmacêuticos, quando os meios de comunicação noticiaram, num período de Março a Julho, que, no armazém farmacêutico central do MISAU, o CMAM,49 em Maputo, havia medicamentos no valor de pelo menos 2 milhões de USD que estavam fora de prazo; que os medicamentos se tinham esgotado nos hospitais públicos na Zambézia; e que grandes quantidades de medicamentos tinham desaparecido da farmácia do Hospital Central de Nampula.50 Os doadores recusaram um pedido de um montante adicional de 25 milhões de dólares para reabastecimento de medicamentos, feito pelo Ministro da Saúde em Março de 2011, argumentando que o governo teria que abordar e resolver as questões pendentes dos resultados da auditoria de 2009, antes de os doadores do PROSAUDE assumirem quaisquer compromissos de financiamento adicionais.51 Em terceiro lugar, pouco antes do fim do ano, o pessoal da saúde na Cidade de Nampula, incluindo os médicos, ameaçaram fazer greve, se não lhes fossem pagos os salários, três meses atrasados. Estes acontecimentos põem em relevo, em síntese, alguns dos principais desafios com que a gestão do sector da saúde se debate em Moçambique. Não se sabe até que ponto estes acontecimentos e o que eles revelam sobre a gestão de recursos no sector da saúde afectaram o funcionamento das unidades de saúde nas províncias e distritos, e o impacto sobre a saúde das pessoas doentes e da população em geral. Estas unidades dependem crucialmente de recursos (pessoal, financiamento e medicamentos) para o cumprimento da sua missão de controlar a doença e salvar vidas humanas, ou seja, para produzir os resultados de saúde que lhes compete alcançar, muitas vezes medidos com o indicador DALY.52 Neste artigo, não tentaremos avaliar o impacto das práticas de gestão no sector da saúde e os seus resultados em termos de vidas humanas. Tentaremos antes entender as dinâmicas políticas, económicas e institucionais que influenciam os resultados de saúde e o desempenho das unidades de saúde ao nível subnacional em Moçambique. O nosso argumento é que estas variáveis são determinadas não apenas por factores endógenos ao sector de saúde, como sejam as suas políticas e quadro regulamentar, a sua estrutura institucional, o grau de descentralização, e ainda os recursos que lhe são atribuídos e as suas capacidades de gestão. Também há factoresexógenos, como as decisões orçamentais do Ministério das Finanças, a Ajuda ao Desenvolvimento da Saúde (ADS)53 por parte dos doadores e as suas políticas e mecanismos de atribuição de fundos, como a abordagem sectorial integrada (SWAp)54 e o financiamento conjunto, bem como a mudança social e económica e as formas de governar um país, que produzem impactos decisivos no sistema de saúde e nos seus resultados. No que diz respeito à temática da descentralização da saúde, partimos, em primeiro lugar, do princípio que os ‘objectivos gerais da descentralização e a abordagem sectorial não são incompatíveis’, uma vez que tanto os primeiros como a segunda ‘têm por objectivo aumentar a eficiência técnica; incentivam uma maior participação; e põem a tónica na transparência e prestação de contas’ (Hutton, 2002: 3. Original em inglês). Em segundo lugar, chamamos a atenção para a necessidade de reconhecer um papel forte e normativo do Estado central nas políticas de saúde, na sua gestão, supervisão e questões de equilíbrio social, especialmente em matéria de cuidados de saúde primários, uma vez que a descentralização pode levar à diferenciação e à diversidade e não ao reforço da justiça social nos padrões e no acesso às unidades de saúde (Collins & Green, 1994). Como Booth sugeriu, o papel do Estado central é fundamental, nomeadamente em institucionalizar e supervisionar, do topo para a base, a disciplina de desempenho eficaz na componente de recursos humanos e na produção de serviços de qualidade a nível local (Booth, 2010: 34). Para este artigo, optámos por usar um quadro da análise político-económica para examinar alguns dos determinantes endógenos e exógenos. Do ponto de vista conceptual, a análise da economia política e da descentralização no sector da saúde pode ser estruturada de várias maneiras. Uma, é analisando as mudanças de epidemiologia, de características biomédicas dos corpos humanos e de ocorrênciaschave nos ciclos da vida humana (por exemplo, a fertilidade, a morbilidade ou mortalidade) como resultantes de intervenções por parte das instituições do sector da saúde, em condições sociais, económicas, ambientais e culturais em mudança. Esta abordagem é muitas vezes centrada na pobreza e assenta no pressuposto de que as mudanças institucionais, como a descentralização da prestação de serviços de saúde, conduzem a um aumento do bem-estar e a uma melhoria da saúde nas sociedades, se as intervenções institucionais (planos, programas, prestadores de serviços, etc.) forem ‘correctos’ e dispuserem de suficientes recursos financeiros e humanos, e capacidades, bem como de um quadro adequado de políticas. Dessa forma, julga-se que as taxas de fertilidade e mortalidade acabarão por diminuir, que as doenças infecciosas serão controladas e podem ser alcançados outros progressos no combate à pobreza e à doença (O’ Laughlin, 2010: 7).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; health / saúde

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

O contexto de REDD+ em Moçambique: Causas, actores e instituições - Sitoe, Almeida; Salomão, Alda; Wertz-Kanounnikoff, Sheila (CIFOR, 2012)
Desde 2009, o CIFOR iniciou o Estudo Comparativo Global de REDD+ (GCS-REDD) em novo países: Bolívia, Brasil, Peru, República dos Camarões, República Democrática do Congo, Tanzânia, Indonésia, Nepal e Vietname. Uma analise parcial é feito em três países: Papua Nova Guiné, Moçambique e Burkina Faso. Depois de analisar políticas nacionais e estratégias emergentes de REDD+, os pesquisadores do CIFOR desenvolveram cinco áreas de trabalho para cada país. Essas áreas incluem um perfil do país, análise de mídia, análise da rede de políticas, análise de conteúdo politico, e uma quinta área de estudos. de políticas específicas, a ser determinada pelos resultados de pesquisas emergentes. Este estudo fornece uma visão geral do contexto de REDD+ em Moçambique através de uma síntese do conhecimento actual das principais causas da mudança de carbono florestal, uma revisão do quadro legal e institucional, e uma descrição do processo político actual de REDD+. O objectivo é reunir dados e informações pertinentes, e oferecer uma análise preliminar dos aspectos fundamentais a ter em conta para políticas de REDD+ eficazes, eficientes e equitativas. Especificamente, este estudo constata que entre os maiores problemas encontra-se a falta de dados sobre o desmatamento e a degradação florestal, fraquezas institucionais (na fiscalização e nos direitos de propriedade) e lacunas na capacidade técnica e humana para enfrentar as exigências ligadas a REDD+. Assim, os resultados eficazes dependerão do grau em que as políticas de REDD+ forem orientadas à mitigação real das fontes de mudança de carbono florestal. Em Moçambique, estas tendem a se originar de fora do sector madeireiro. O custo-eficácia dos resultados dependerá de se as causas fundamentais da mudança de carbono florestal são identificadas e tratadas com opções políticas mais viáveis de REDD+; da capacidade do governo de responder às exigências de REDD+, sobretudo a nível subnacional, mas também da capacidade da sociedade civil e outras instituições; e da força do quadro institucional. O grau de sucesso dos resultados equitativos e a geração de co-benefícios dependerá se os processos são inclusivos e realmente apropriados nacionalmente; se aqueles que suportam os custos de REDD+ também estão sendo compensados; e da definição sobre os direitos do carbono e dos serviços ambientais em geral
Keywords: G - Mozambique / Moçambique; L - portuguese / português

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ------- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde

The White Gold: The Role of Government and State in Rehabilitating the Sugar Industry in Mozambique - Buur, Lars; Mondlane Tembe, Carlota; Baloi, Obede (The Journal of Development Studies, 2012)
This article examines the rehabilitation of the sugar industry in Mozambique after the General Peace Accord in 1992, engaging primarily and critically with certain aspects of the business-state literature. It explains why the sugar sector was rehabilitated from the perspectives of Mozambican state, government and industry actors. The article argues that support for the industry cannot be identified in singular and one-dimensional terms, but must include a variety of attributes of support that emerged from a post-independence fusion of industry, state and government officials' historical experiences of success and failure in the industry, and pragmatic as well as longer-term ideological stances. This, it is argued, created a ‘mediating bureaucracy’ that could broker between the diverse interests and aspirations of state/government and industry.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - Weimer, Bernhard; Cumbi, Amelia J.; Macuane, José Jaime (MAP Consult, 2012)
The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; health / saúde

Gender Disparity in Laws and Female Employment - Amin, Mohammad (Mimeograph, 2012)
Berkeley Electronic Press Selected Works, In a large sample of firms in 66 developing countries, it is shown that gender specific disparity in the laws favoring males over females tends to lower the employment of females relative to males at the firm level. However, this relationship between gender disparity in laws and employment is driven by small and medium firms, and it does not hold for the sample of large firms. However, the relationship holds equally in rich vs. poor countries, small vs. large cities within countries and among firms with and without female owners. We also confirm a sharp negative effect of gender disparity in the laws on the absolute level of employment of females. In short, in the presence of gender disparity in the laws, suitable reforms or policy measures promoting female employment may be required to achieve greater employment of women and greater gender parity in employment.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Effects of food price shocks on child malnutrition: the Mozambican experience 2008/09 - Arndt, Channing; Hussain, M. Azhar; Østerdal, Lars Peter (World Institute for Development Economics Research (WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Mozambique’s Coming Natural Resource Boom Expectations, Vulnerabilities, and Policies for Successful Management - Biggs, Tyler (USAID, 2012)
Mozambique is set to become a world-class natural resource exporter with projections indicating that it will experience rapid increases in windfall revenues over the next several decades and well beyond. While this is welcome news for a low-income country with a substantial proportion of the population below the poverty line, it foreshadows some economic management problems ahead. The main concern is the poor economic record of many other lowincome countries with large natural resource endowments. It is remarkable how often these countries have experienced inferior rates of growth compared with countries lacking such endowments. This pattern, known as the ―natural resource curse,‖ has been documented in empirical research across a wide sample of nations.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural disasters / desastres naturais

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Desafios para Moçambique - 2012 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2012)
PARTE I – POLÍTICA POBREZA, “PARPAS” EGOVERNAÇÃO / Luís de Brito A DESCENTRALIZAÇÃO AJUDA A REDUZIR A POBREZAPOLÍTICA EM MOÇAMBIQUE? / Joao C.G. Pereira APRENDIZADO DE POLÍTICAS PÚBLICAS NO CONTEXTO DO PARP:ABORDAGEM BASEADA NAS REDES / José Jaime Macuane UNIVERSIDADES MOÇAMBICANAS E O FUTURO DE MOÇAMBIQUE / Lourenço do Rosário PARTE II – ECONOMIA PARP 2011-2014: CONTRADIÇÕES, TENSÕES E DILEMAS/ Carlos Nuno Castel-Branco DA ECONOMIA EXTRACTIVA À DIVERSIFICAÇÃO DA BASE PRODUTIVA:O QUE PODE O PARP UTILIZAR DA ANÁLISE DO MODO DE ACUMULAÇÃO EM MOÇAMBIQUE? / Carlos Nuno Castel-Branco | Oksana Mandlate SERÁ A ITIEM RELEVANTE PARA MELHORAR A GESTÃO DOS RECURSOS MINERAIS?UMA ANÁLISE CRÍTICA DA EXPERIÊNCIA / Rogério Ossemane AGRICULTURA, POBREZA E A RECEITA DO PARP /Philip Woodhouse POLÍTICA MONETÁRIA E REDUÇÃO DA POBREZA EM MOÇAMBIQUE: DISCUSSÃO CRÍTICA / Carlos Nuno Castel-Branco | Rogério Ossemane DESAFIOS DE DESENVOLVIMENTO DA BASE PRODUTIVA: UM OLHAR A PARTIR DO PARP 2011-2014 / Carlos Muianga OPÇÕES DE FINANCIAMENTO DO INVESTIMENTO PÚBLICO: UM OLHAR CRÍTICO SOBRE O PARP 2012-14 / Sofia Amarcy MEGA-PROJECTOS NO MEIO RURAL, DESENVOLVIMENTO DO TERRITÓRIO E POBREZA: O CASO DE TETE / João Mosca | Tomás Selemane PARTE III – SOCIEDADE POLÍTICA PÚBLICA E INTERVENCIONISMO: PORQUE EXISTE O PARP EM MOÇAMBIQUE? / António Francisco IDOSOS EM MOÇAMBIQUE: ROMPER A CONSPIRAÇÃO DO SILÊNCIO / Gustavo Sugahara | António Francisco O DESAFIO DA SAÚDE RURAL / Bridget O’Laughlin REFLEXÕES SOBRE EMPREGO E REDUÇÃO DA POBREZA NO PARP: DESAFIOS PARA UMA ABORDAGEM ALTERNATIVA / Yasfir Ibraimo PARTE IV – MOÇAMBIQUE NO MUNDO CRISE GLOBAL, CRESCIMENTO E DESAFIOS PARA MOÇAMBIQUE E SUA ESTRATÉGIA DE DESENVOLVIMENTO / Carlos Oya INVESTIMENTO DIRECTO ESTRANGEIRO E O COMBATE À POBREZA EM MOÇAMBIQUE: UMA LEITURA A PARTIR DO INVESTIMENTO CHINÊS NA AGRICULTURA / Sérgio Chichava
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Mozambique Social Protection Assessment - Review of Social Assistance Programs and Social Protection Expenditures - Marques, José Silvério (World Bank, 2012)
This assessment shows that Mozambique social protection system is developing. While programs to address most of the risks identified exist, there are still major gaps. Poor families with children are not adequately supported, there is no significant youth program, and subsistence farmers and other workers are not properly protected against recurrent shocks. The government spends a considerable amount of its resources on social protection but most are absorbed by untargeted subsidies and pensions that benefit only a few. This assessment suggests that it will be necessary to address three mutually complimentary issues: developing effective mechanisms to maximize the impact of social protection on reducing poverty; rationalizing public expenditures while filling existing program gaps; and strengthening institutional arrangements. In order to address the multiple challenges Mozambique faces to support particularly vulnerable groups and reduce extreme poverty and food insecurity, the report proposes a gradual approach framed in the existing social protection strategy approved by the Government in 2010.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

From Negligence to Populism: An Analysis of Mozambique’s Agricultural Political Economy - Rosário, Domingos Manuel do (2012)
The paper analyses the changing configuration of the political system since the Rome Peace Agreement of 1992. It discusses how the “political settlement” underlying the Peace Agreement and the outcomes of multiparty elections thereafter have shaped governance, including policy-making concerning the agriculture sector and the rural economy. The paper argues that private interests and electoral objectives have been important drivers of policy decisions taken by the governing elites concerning the agriculture sector and local governance, with precedence over donor influence. By contrasting the political choices and governance approaches adopted by the two different presidential administrations in office since the first multiparty elections were held in 1994, it is argued that one (led by Joaquim Chissano) is marked by features of “neopatrimonialism”, whereas the other (led by Armando Guebuza) is showing signs of electoral “populism”. The former is characterised by significant rent distribution by the governing elite to a narrow “selectorate”. The latter is manifested by a paternalistic and politically mobilising discourse emanating directly from the President and appealing to the broader electorate, particularly the rural population of the central and Northern region of the country, who has been traditionally opposed to the ruling party
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza